Physiological and proteomic approaches to address the active role of botrytis cinerea inoculation in tomato postharvest ripening - Tzortzakis, Nikos G. (My University, 2019)
Botrytis cinerea is an unbearable postharvest threat with significant economic impacts. Necrotrophic B. cinerea can readily infect ripe fruit resulting in the rapid progression of symptoms of the disease. To unravel the mechanism by which tomato fruit opposes pathogen attack, we investigated the changes in quality‐related attributes as a direct response (DR) or systemic response (SR) of infected tomatoes to the B. cinerea. Additionally, the SR of protein yield and composition were studied in fruit stored at 11 °C/90% relative humidity (RH) for one week. Fungal infection accelerated ripening with increased ethylene and respiration rates. Fruit softening, ascorbic acid and β‐carotene increase were associated with DR but not with the SR of the pathogen. Pathogen infection increased lipid peroxidation, causing the production of hydrogen peroxide and oxidative stress, as fruit activated both enzymatic and non‐enzymatic mechanisms to trigger stress. B. cinerea increased up to 6.6% the protein yield and downregulated at least 39 proteins. Proteins involved in fruit ripening, such as an ethylene biosynthetic enzyme, were increased in wound‐inoculated fruit. Moreover, antioxidant proteins, such as ascorbate peroxidase‐APX1 and superoxide dismutase‐ SOD, increased in infected tomatoes, as these proteins are involved in reactive oxygen species detoxification. Constitutively‐expressed proteins tended to be either increased (chaperonin and malate dehydrogenase) or remained unaffected (dehydrin) by pathogen inoculation. Protein levels involved in the metabolism of carbohydrate, the pentose phosphate pathway, terpenoid and flavonoid biosynthesis were differently affected during the treatments. By enabling a better understanding of the fungal direct or systemic response on fruit quality and ripening through biochemical and proteome studies, we may improve the plant–pathogen interaction and complexity.
Keywords: Gray mould; Proteomics; Quality; Storage; Tomato fruit